Studi Kekuatan Support Structure (Leg) pada Konstruksi FPSO Bulk Water Separation Module - Surya Lesmana; Mufti Fathonah Muvariz; Nurul Fadilah; Hendra Saputra; Sapto Wiratno Satoto (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
The Support Structure is a part of the structure that provides rigidity and strength and supports the weight of the load above it. The initial design in this study uses CAD which is then converted to SolidWorks 2019 for simulation. The weight of the load generated for testing the support structure comes from the weight of the module construction above it of 30,925 kg, assumed to be a static load. The material that is part of the support structure in this study is S355J0-type structural steel with a yield strength value of 275 N/mm2. Stress testing shows that the maximum stress is 198 N/mm2 so it can be categorized as safe because x < the yield strength value. Strain testing shows a maximum value of 5.260 × 10-4, while the maximum displacement is 1.168 mm. The factor of safety testing with simulation showed a result of 1.4